Research for applications of RFID in Chengdu and innovation designing based on TRIZ - Fan Yang; Feng-Li Zhang (2010 International Conference on Apperceiving Computing and Intelligence Analysis, 2010)
The purpose of this paper, as a first stage, is to identify or imagine, some applications based on RFID that could be useful to simplify working systems in Companies or to make easier the daily life of persons in the area of Cheng Du. A second stage, will be to make an inventory as wide as possible of the existing similar process through the world, and using a TRIZ method (algorithm for inventive problem solving) in order to find the basis concepts that could be adapted to our particular issues. Further developments of this study could be in view, such as designing specialised tags using an Innovation Design for Internet of Things (IoT) or later the transmission of data and information through a cloud computing system for a wide utilization. A second stage, will be to make an inventory as wide as possible of the existing similar process through the world, and using a TRIZ method (algorithm for inventive problem solving) in order to find the basis concepts that could be adapted to our particular issues. Further developments of this study could be in view, such as designing specialised tags using an Innovation Design for Internet of Things (IoT) or later the transmission of data and information through a cloud computing system for a wide utilization.